Implantation of a denaturated cellulose adhesion barrier after plate osteosynthesis of finger proximal phalangeal fractures: results of a randomized controlled trial. (May 2016) - Kappos, E. A.; Esenwein, P.; Meoli, M.; Meier, R.; Grünert, J.
Adhesions after osteosynthesis of finger proximal phalangeal fractures often cause stiffness. To minimize adhesions, the use of an adhesion barrier has been proposed. The results until now have not been convincing. The aim of this prospective randomized trial was to evaluate the use of an adhesion barrier. The trial included any isolated, closed proximal phalangeal fracture needing plate osteosynthesis. The patients were randomized into two groups: with or without application of the adhesion barrier. The outcomes we measured were finger ranges of motion and DASH score at 6 weeks and 6 months post-operatively. A total of 42 patients (42 fingers) entered the study; 37 completed the study. The key baseline characterisitcs were comparable. At 6 weeks there was a trend favouring the adhesion barrier that disappeared at 6 months. Overall the results do not support the use of this device. Level of evidence: II.